Recognition of American sign language hand gestures - Ting, Allan T.; Landicho, Joy DC.; Ibarrola, Ma. Gina M.; Aranzaso, Noel B. (2000)
Hand gesture in a natural form of communication that humans use everyday. Yet the most popular mode of Human Computer Interaction (HCI) is based on simple devices such as keyboards and mice. These devices have grown to be familiar but also limit the speed and naturalness with which we can interact with the computer. The use of hand gestures provides an alternative to interface devices for HCI and has motivated a very active research area concerned with computer vision-based analysis and interpretation of hand gestures. Several classes of hand gesture interface techniques has been explored such as glove-based techniques, visio-based techniques, techniques that use drawing gestures and other gestures analysis techniques. In this paper we present an application that recognizes hand gestures by using appearance-based analysis. We used the SGI Workstation and its video camera to capture the image we need to analyze. This is then passed to a program that utilizes the Self Organizing Map for segmentation of the moving hand from complex background, analysis of hand motion and tracking of hand position. Finally these images are used as inputs for the feedforward neural network that uses the backpropagation algorithm to tune its weights for the recognition of hand gestures. This network then outputs the recognized gesture and displays it on the screen. Although we were successful in producing an accurate network, a number of revisions can be done to further improve and produce an effective and natural hand gesture interface.
Thesis (B.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Gesture -- Data processing; American sign language; Human-computer interaction; Hand gesture recognition .; Sign language recognition